Swift J053041.9-665426, a new Be/X-ray binary pulsar in the Large Magellanic Cloud - Vasilopoulos, G.; Maggi, P.; Haberl, F.; Sturm, R.; Pietsch, W.; Bartlett, E. S.; Coe, M. J. (2013)
Aims: We observed the newly discovered X-ray source Swift J053041.9-665426in the X-ray and optical regime to confirm its proposed nature as a high mass X-ray binary. Methods: We obtained XMM-Newton and Swift X-ray data, along with optical observations with the ESO Faint Object Spectrograph, to investigate the spectral and temporal characteristics of Swift J053041.9-665426. Results: The XMM-Newton data show coherent X-ray pulsations with a period of 28.77521(10) s (1σ). The X-ray spectrum can be modelled by an absorbed power law with photon index within the range 0.76 to 0.87. The addition of a black body component increases the quality of the fit but also leads to strong dependences of the photon index, black-body temperature and absorption column density. We identified the only optical counterpart within the error circle of XMM-Newton at an angular distance of ~0.8'', which is <ASTROBJ>2MASS J05304215-6654303</ASTROBJ>. We performed optical spectroscopy from which we classify the companion as a B0-1.5Ve star. Conclusions: The X-ray pulsations and long-term variability, as well as the properties of the optical counterpart, confirm that <ASTROBJ>Swift J053041.9-665426</ASTROBJ> is a new Be/X-ray binary pulsar in the Large Magellanic Cloud. Based on observations with XMM-Newton, an ESA Science Mission with instruments and contributions directly funded by ESA Member states and the USA (NASA).
Keywords: Astrophysics - High Energy Astrophysical Phenomena; Be; galaxies: individual: Large Magellanic Cloud; pulsars: individual: Swift J053041.9-665426; stars: emission-line; stars: neutron; X-rays: binaries